Effect of some plant powders on grain microflora of paddy during storage - T. RATNASUDHAKAR, V. KRISHNA RAO* and (Indian Phytopathology, 2002)
The effect of rhizome powder of Acorus calamus and leaf powder of Azadirachta indica, separately and in combination at 1 and 2 per cent concentration (w/w) on fungal and bacterial population associated with paddy during storage was studied. The results showed that A. calamus at 2 per cent was most effective in reducing the both fungal and bacterial population. Mixing of plant powder to paddy did not show any adverse effect on quality of cooked rice.